A water story : learning from the past, planning for the future - Beeson, Geoff (CSIRO Publishing, 2020)
"A comprehensive and engaging account of water use in Australia, from Ancient Australia to today. Freshwater scarcity is a critical challenge, with social, economic, political and environmental consequences. Water crises in Australia have already led to severe restrictions being applied in cities, drought ravaging farmlands, and the near-terminal decline of some rivers and wetlands. A Water Story provides an account of Australian water management practices, set against important historical precedents and the contemporary experience of other countries. It describes the nature and distribution of the country's natural water resources, management of these resources by Indigenous Australians, the development of urban water supply, and support for pastoral activities and agricultural irrigation, with the aid of case studies and anecdotes. This is followed by discussion of the environmental consequences and current challenges of water management, including food supply, energy and climate change, along with options for ensuring sustainable, adequate high-quality water supplies for a growing population."--CSIRO Publishing Website